Coexistence of lung cancer in a patient with non-tuberculous mycobacteria - Vinod, Sushmita; Ganesan, Natesh; Sowmitha S. G.; Vadivelu, Gangadharan (International Journal of Advances in Medicine, 2023)
Nontuberculous mycobacteria (NTM) may mimic lung carcinoma as a solitary mass or miliary nodules, the coexistence of NTM and lung carcinoma is rare. The diagnosis may be delayed due to a high initial index of suspicion for mycobacterium tuberculosis complex rather than malignancy in an endemic country like India. We report a rare case of 47-year-old male who presented with exertional dyspnea, cough with expectoration and fever was initially treated with anti-tuberculous drugs following a mycobacterium avium complex growth in BAL cultures. Despite treatment, patient’s condition worsened, and computed tomography (CT) guided biopsy was done which showed adenocarcinoma. This case report highlights that a lung biopsy is a necessity for accurate diagnosis, and a positive NTM culture doesn't always exclude a concomitant lung carcinoma.